Intercultura e inclusione Il Cooperative Learning nella classe plurilingue - Chiappelli, Tiziana (La melagrana - Open Access, 2016)
This volume offers a theoretical framework, numerous evidences and a series of hints to work in a multilingual and multicultural classroom, offering teachers, educators and experts tools consistent with the vision of "a school for all and for everyone".